2010
DOI: 10.1161/hypertensionaha.109.140988
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Spironolactone Therapy in Patients With True Resistant Hypertension

Abstract: Abstract-The role of spironolactone in resistant hypertension management is unclear. The aim of this prospective trial was to evaluate the antihypertensive effect of spironolactone in patients with true resistant hypertension diagnosed by ambulatory blood pressure monitoring. A total of 175 patients had clinical and complementary exams obtained at baseline and received spironolactone in doses of 25 to 100 mg/d. A second ambulatory blood pressure monitoring was performed after a median interval of 7 months. Pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
126
4
15

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(148 citation statements)
references
References 35 publications
3
126
4
15
Order By: Relevance
“…29 Previous trials reported conflicting data about whether the BP response to spironolactone can be predicted by baseline aldosterone, ARR, or baseline potassium. 10,21,23,30,31 In our trial, the BP response to spironolactone treatment in patients with baseline ARR Յ7 and PRA Ͼ1.34 ng/mL per hour was significantly worse than the BP response of patients with ARR Ͼ7 and PRA Յ1.34 ng/mL per hour. This could possibly help to identify the patients for which treatment with spironolactone is most effective.…”
Section: Discussionmentioning
confidence: 51%
“…29 Previous trials reported conflicting data about whether the BP response to spironolactone can be predicted by baseline aldosterone, ARR, or baseline potassium. 10,21,23,30,31 In our trial, the BP response to spironolactone treatment in patients with baseline ARR Յ7 and PRA Ͼ1.34 ng/mL per hour was significantly worse than the BP response of patients with ARR Ͼ7 and PRA Յ1.34 ng/mL per hour. This could possibly help to identify the patients for which treatment with spironolactone is most effective.…”
Section: Discussionmentioning
confidence: 51%
“…This underscores the contributory role of relative aldosterone excess to treatment resistance, such that even those with presumably low levels of aldosterone benefit from mineralcorticoid receptor antagonists use. (Nishizaka et al, 2003;Sartori et al, 2006;De Souza et al, 2010) This is in contrast with other studies that showed that high ARR predicted the antihypertensive efficacy of spironolactone (Eide et al, 2004); these contrasting results may be explained by the considerably higher spironolactone dose administered in patients with demonstrated PA, generating a strong difference in the two populations.…”
Section: Mineralocorticoid Receptor Antagonistscontrasting
confidence: 87%
“…24 However, the long-term use of this treatment strategy has only been established during the last several years. In their open label study population of 175 patients with resistant hypertension additionally treated with spironolactone for >1 year, de Souza et al 25 reported further impressive BP reductions, averaging 16/9 mm Hg.…”
Section: The Role Of Aldosterone In the Presentation Of Resistant Hypmentioning
confidence: 96%